KEEPING GOLIATH ON HIS TOES: A CASE-DISCUSSION METHOD FOR INCREASING ENGAGEMENT AND INDIVIDUAL ACCOUNTABILITY IN LARGE CLASSES. Issue 2 (4th May 2018) - Harding, Lora Mitchell
Abstract : Application-based assignments are often forgone in large marketing classes because of the daunting implementation and assessment challenges they present. One solution is to divide large classes into groups, but groups present their own challenges—of note, the potential for students to free-ride on the efforts of others. The 4Ps method of case discussion was developed to keep students in large classes engaged and accountable while minimizing the grading burden on instructors. Indeed, the 4Ps method not only enables students to apply marketing concepts through stimulating case-based discussions, it also improves perceived and actual learning outcomes while keeping grading manageable.